Ureteral fibroepithelial polyp: A diagnostic challenge - Raj A. Kumar (Elsevier, 2022)
Ureteral fibroepithelial polyps (UFP) are relatively rare, benign tumors. A total of 236 total cases were documented between 1932 and 2013. Notably, imaging studies, including computerized tomography (CT) and magnetic resonance imaging (MRI) are often negative. This report details a case of a patient with a UFP who presented with hematuria. CT suggested a possible 1.8 cm mass, but subsequent MRI was negative. Cystoscopy showed a polyp that prolapsed out of the left ureter and into the bladder with peristalsis. The patient subsequently underwent retrograde ureteroscopy and holmium laser excision of the polyp.